TNF-α signaling: TACE inhibition to put out the burning heart - Dittrich, Gesine M.; Heineke, Jörg (PLoS biology, 2020)
More than 20 years ago, Seta and colleagues hypothesized that cytokines, which are activated by myocardial injury, significantly drive heart failure progression and would therefore be effective targets to treat cardiac dysfunction. Unfortunately, several clinical trials inhibiting key cytokines like tumor necrosis factor alpha (TNF-α) and interleukin 1 beta (Il-1β) turned out negative or even revealed adverse clinical effects. Providing a potential mechanistic explanation for the ineffectiveness of TNF-α blockade in heart failure, novel findings demonstrate that the membrane-bound precursor form of TNF-α, transmembrane TNF-α (tmTNF-α), mediates cardioprotective effects during pressure overload-induced cardiac remodeling. This study suggests that preventing tmTNF-α cleavage by targeting the TNF-α converting enzyme (TACE) rather than inhibiting TNF-α signaling altogether might be a valuable therapeutic approach.